PENGARUH E MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PRODUK NUFACE PADA GENERASI Z DI PLATFORM E COMMERCE SHOPEE - Adian Adelia; Dian Wahyuni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to determine the simultaneous and partial effects of the e-marketing mix (E-Product, E-Price, E-Promotion, E-Place, People, Process, and physical evidence) on purchase decisions for Nuface products among Generation Z on the Shopee e-commerce platform. The research employed a quantitative descriptive method, and the data were analyzed using multiple linear regression analysis. The sampling technique used in this study was purposive sampling, which involves selecting respondents based on specific criteria in accordance with the research objectives. Since the population size was not precisely known, the sample size was determined using the Lemeshow formula, resulting in a total sample of 96 respondents. Validity and reliability tests were also conducted on respondents outside the research sample. The results of the multiple linear regression analysis produced the following equation: Y = 0.195 + 0.059 X1 ? 0.186 X2 + 0.631 X3 + 0.680 X4 + 0.009 X5 + 0.281 X6 + 0.460 X7 + e. The findings indicate that, simultaneously, the e-marketing mix variables (E-Product, E-Price, E-Promotion, E-Place, People, Process, and physical evidence) significantly influence purchase decisions for Nuface products among Generation Z on the Shopee e-commerce platform. Partially, most variables have a positive effect on purchase decisions, except for the E-Price variable, which has a negative effect on purchase decisions. Based on the regression coefficient values obtained, the E-Place variable is the most dominant factor influencing purchase decisions, as it has the largest coefficient value compared to the other variables. Keywords: E-Marketing Mix, E-Product, E-Price, E-Promotion, E-Place, People, Process, Physical Evidence, Purchase Decision   Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh secara simultan dan parsial e-marketing mix (E-Product, E-Price, E-Promotion, E-Place, People, Process, dan physical evidence) terhadap keputusan pembelian produk Nuface pada Generasi Z di platform e-commerce Shopee. Jenis penelitian yang digunakan adalah deskriptif kuantitatif dengan analisis data menggunakan regresi linear berganda. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah teknik purposive sampling, yaitu penentuan responden berdasarkan kriteria tertentu yang sesuai dengan tujuan penelitian. Karena jumlah populasi tidak diketahui secara pasti, maka penentuan jumlah sampel dihitung menggunakan rumus Lemeshow, dengan jumlah sampel sebanyak 96 responden. Uji validitas dan reliabilitas juga dilakukan terhadap responden diluar sampel penelitian. Hasil analisis regresi linear berganda diperoleh persamaan sebagai berikut: Y = 0,195 + 0,059 X1 - 0,186 X2 + 0,631 X3 + 0,680 X4 + 0,009 X5 + 0,281 X6 + 0,460 X7 + e. Hasil penelitian menunjukkan bahwa secara simultan variabel e-marketing mix (E-Product, E-Price, E-Promotion, E-Place, People, Process, dan physical evidence) berpengaruh terhadap keputusan pembelian produk Nuface pada Generasi Z di platform e-commerce Shopee. Secara parsial, sebagian besar variabel memiliki pengaruh positif terhadap keputusan pembelian, kecuali variabel E-Price yang memiliki pengaruh negatif terhadap keputusan pembelian. Berdasarkan nilai koefisien regresi yang diperoleh, variabel E-Place merupakan variabel yang paling dominan mempengaruhi keputusan pembelian karena memiliki nilai koefisien terbesar dibandingkan variabel lainnya. Kata Kunci: E-Marketing Mix, E-Product, E-Price, E-Promotion, E-Place, People, Process, Physical Evidence, Keputusan Pembelian